Early Intervention and Its Impact on the Cognitive Development of Children with Down Syndrome - Shazia Afzal (CV. RADJA PUBLIKA, 2025)
Due to genetic and neurological reasons, children with Down Syndrome (DS) are quite likely to have cognitive deficits. This study report examines the importance of early intervention in improving the cognitive development of children with Down syndrome. Based on a thorough analysis of empirical data, the study analyzes the favorable effects of early therapies—such as physical, speech, occupational, and educational interventions—on cognitive processes including memory, attention, language, and executive abilities. Results show that treatments started in the first five years of life can greatly increase intellectual functioning, school preparation, and adaptive behaviors. The study emphasizes the significance of interdisciplinary, family-centered, and personalized strategies in optimizing developmental outcomes for children with Down syndrome. Policy suggestions are made to make early intervention programs easier to use, better, and more successful.